Social, Economic, and Health Empowerment in Pandeglang through a Community-Based Model - Syarifudin, Efi; Sugondo, Sigit Iko; S. Ndolu, Juliana (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
Community-based empowerment is crucial in enhancing social, economic, and health conditions, particularly in rural areas such as Pandeglang. This study explores a community-based model's impact on improving residents' well-being by fostering economic resilience, social cohesion, and health awareness. Through participatory approaches, including capacity-building programs, entrepreneurship training, and health education, this research aims to assess the effectiveness of community-driven initiatives in creating sustainable development. Data collection involves surveys, interviews, and field observations involving key stakeholders such as local government, community leaders, and beneficiaries. The findings indicate that active community participation, supported by strategic collaborations, significantly enhances economic productivity, strengthens social networks, and improves health outcomes. The study concludes that a well-structured community-based model is a sustainable framework for addressing socio-economic and health challenges in Pandeglang, providing valuable insights for policymakers and development practitioners.